PENGARUH CAMPURAN SERBUK KAYU TERHADAP KUAT TEKAN BETON - Sukmawan Gulo, Boby; Halawa, Nopesman (Departement of Civil Engineering, Universitas Winaya Mukti, 2024)
In the construction project of RSU D Pratama in Nias Regency, this study aims to identify variables that increase the risk of work accidents. The author of this study used quantitative methods. The aspects used by researchers to identify the risk of work accidents include Factors of Work Accidents, Factors Causing Disease, Factors Causing Work Accident Hazards in Development Construction Projects, and Protection Factors for the Application of Occupational Safety and Health. Based on the results of the study, almost all aspects of the Class D Primary Hospital building in Nias Regency have occupational accident risks that have an impact on Occupational Safety and Health (K3).